Discovery of carbon-based strongest and hardest amorphous material. Issue 1 (5th August 2021) - Zhang, Shuangshuang; Li, Zihe; Luo, Kun; He, Julong; Gao, Yufei; Soldatov, Alexander V; Benavides, Vicente; Shi, Kaiyuan; Nie, Anmin; Zhang, Bin; Hu, Wentao; Ma, Mengdong; et al.
Abstract: Carbon is one of the most fascinating elements due to its structurally diverse allotropic forms stemming from its bonding varieties ( sp, sp 2 and sp 3 ). Exploring new forms of carbon has been the eternal theme of scientific research. Herein, we report on amorphous (AM) carbon materials with a high fraction of sp 3 bonding recovered from compression of fullerene C60 under high pressure and high temperature, previously unexplored. Analysis of photoluminescence and absorption spectra demonstrates that they are semiconducting with a bandgap range of 1.5–2.2 eV, comparable to that of widely used AM silicon. Comprehensive mechanical tests demonstrate that synthesized AM-III carbon is the hardest and strongest AM material known to date, and can scratch diamond crystal and approach its strength. The produced AM carbon materials combine outstanding mechanical and electronic properties, and may potentially be used in photovoltaic applications that require ultrahigh strength and wear resistance. Abstract : The currently synthesized semiconducting amorphous carbon form is the hardest and strongest amorphous material known to date, and has a bandgap comparable to that of amorphous silicon.